Debt Levels and Their Effect on The Profitability of Banking Firms at The Indonesia Stock Exchange - Rachmawati Rachmawati; Muhammad Faried Pratama; Sri Rachmawati Rachman; Sumaria Hisa (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study aims to determine the impact of debt levels on the profitability of banking companies listed on the Indonesia Stock Exchange. The research focuses on two variables: the Debt-to-Equity Ratio (DER) and Return on Assets (ROA). Quantitative research with simple linear regression analysis is a type of study aimed at understanding the relationship between two variables. The population of this study includes 47 banking companies listed on the Indonesia Stock Exchange (IDX), from which a sample of 4 banking companies was selected using purposive sampling. This qualitative research employs simple linear analysis using SPSS 25.0 as the analytical tool. The results, based on significant values and partial values, indicate that an increase in debt levels among banking companies listed on the Indonesia Stock Exchange leads to a decrease in profitability. This is because the debt of banking companies is not solely used for operational activities but also for providing credit funds to customers